Digital Readiness Catalyzing Halal Practices and Digital Payment for MSME Financial Performance - Rachmaniar Myrianda Dwiputri; Ike Irawati; Eka Pariyanti; Agapito Barros (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines how halal practices and digital payment adoption influence the financial performance of micro and small enterprises. The increasing integration of halal standards and digital technology in business operations raises questions about how these factors jointly contribute to performance, particularly in transaction-intensive sectors. Design/methodology/approach – A quantitative approach was employed using survey data collected from 167 micro and small enterprise owners in Bekasi City. Data were analyzed using Structural Equation Modeling (SEM) to test direct, mediating, and moderating relationships among variables. Finding/Results – The results show that halal practices positively affect financial performance, while digital payment does not have a direct effect. Transaction efficiency significantly improves financial performance and mediates the effects of both halal practices and digital payment. Digital readiness strengthens the relationships between halal practices, digital payment, and transaction efficiency. Originality/Value – This study highlights the critical role of transaction efficiency as a mechanism linking operational practices and technology to financial outcomes. It also emphasizes digital readiness as a key capability that enhances the effectiveness of both halal compliance and digital payment adoption in improving MSME performance.